Dilemmas of Co-production: How Street Waste Pickers Became Excluded from Inclusive Recycling in São Paulo. (May 2022) - Rosaldo, Manuel
ABSTRACT: Under what conditions do collaborations between informal workers and the state in public service provision lead to socially beneficial synergies, and when might they intensify inequalities? This article, based on 14 months of ethnographic research, addresses this question through a comparative case study of two attempts to co-produce recycling services in São Paulo. The first, a grassroots organizing effort in the 1980s and 1990s, improved the incomes and conditions of hundreds of waste pickers and inspired a national upsurge of waste picker organizing. The second, an ambitious overhaul of waste management in the early 2000s, generated about 1, 500 jobs but functionally excluded the very population of street waste pickers it was designed to benefit. The findings suggest that co-production is most likely to lead to pro-poor outcomes if concerted efforts are made to level inequalities between poor constituents and more powerful stakeholders during processes of policy design and implementation.